To generate an equivalent expression for \( \frac{3^{\sqrt{8}}}{\sqrt{2}} \) using properties of exponents, follow these steps:
-
Rewrite the square roots as exponents:
\[
\sqrt{8} = 8^{1/2} \quad \text{and} \quad \sqrt{2} = 2^{1/2}
\]
So, we can rewrite the expression:
\[
\frac{3^{\sqrt{8}}}{\sqrt{2}} = \frac{3^{8^{1/2}}}{2^{1/2}}
\]
-
Simplify \( \sqrt{8} \):
\[
\sqrt{8} = \sqrt{4 \times 2} = \sqrt{4} \cdot \sqrt{2} = 2\sqrt{2}
\]
Thus, we rewrite \( 3^{\sqrt{8}} \) as:
\[
3^{\sqrt{8}} = 3^{2\sqrt{2}} = (3^{\sqrt{2}})^2
\]
-
Combine the expression:
Now we can combine both parts:
\[
\frac{(3^{\sqrt{2}})^2}{2^{1/2}}
\]
Putting it all together, we end up with the equivalent expression:
\[
\frac{(3^{\sqrt{2}})^2}{2^{1/2}} = (3^{\sqrt{2}})^2 \cdot 2^{-1/2}
\]
Thus, the final expression can be written in an alternative simplified form:
\[
(3^{\sqrt{2}})^2 \cdot \frac{1}{\sqrt{2}} \quad \text{or} \quad \frac{(3^{\sqrt{2}})^2}{\sqrt{2}}
\]